W.W. Corcoran papers - Corcoran, W. W. (William Wilson), 1798-1888.; Corcoran, Thomas, 1754-1830.
Correspondence, letterpress books, financial records, newspaper clippings, printed matter, and other papers relating primarily to Corcoran's business and banking interests and philanthropic efforts. Documents his involvement with the brokerage and banking firms, Corcoran & Riggs, Washington, D.C.; Riggs and Co, New York, N.Y.; Bank of America; and Wilson, Colston & Co., Baltimore, Md. Also documents his investment ventures in the Baltimore and Ohio Railroad Company; Chesapeake and Ohio Canal Company; Little Miami Railroad Company; Philadelphia, Wilmington, and Baltimore Rail Road Company; California and Texas debts; Dubuque, Iowa, bonds; the "Great Superior Scheme" in Wisconsin; and Mississippi land holdings. Includes material pertaining to the Corcoran Gallery of Art; Louise Home, Washington, D.C.; and social life in Washington, D.C. Also includes correspondence and financial records of Corcoran's father, Thomas Corcoran.
Correspondents include William Aiken, George Bancroft, August Belmont, John C. Breckinridge, Arthur Brice, Jesse D. Bright, James Buchanan, Thomas Green Clemson, Leslie Combs, Jefferson Davis, John Wesley Davis, Daniel S. Dickinson, Stephen A. Douglas, Alexander Doyle, Edward Everett, Moses Jacob Ezekiel, Millard Fillmore, John W. Forney, Edward Miner Gallaudet, John Lane Gardner, Friedrich Karl Joseph von Gerolt, Ransom H. Gillet, Gabriel Harrison, Joseph Henry, Alexander von Humboldt, R.M.T. Hunter, Anthony Hyde, Robert Ward Johnson, George Wallace Jones, J. William Jones, Amos Kendall, Charles Lanman, Robert E. Lee, J.M. Mason, Junius Spencer Morgan, George Peabody, James Renwick, Elisha Riggs, Lawrason Riggs, David Rorer, Philip Slaughter, William Wetmore Story, Aaron Vail, Charles S. Venable, Robert J. Walker, Daniel Webster, James Grant Wilson, and Robert C. Winthrop.
Microfilm edition of letterbook indexes available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Financier and philanthropist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aiken, William, -- 1806-1887 -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Belmont, August, -- 1816-1890 -- Correspondence; Breckinridge, John C. -- 1821-1875 -- Correspondence; Brice, Arthur -- Correspondence; Bright, Jesse D. -- 1812-1875 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Clemson, Thomas Green, -- 1807-1888 -- Correspondence; Combs, Leslie, -- 1793-1881 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Davis, John Wesley, -- 1799-1859 -- Correspondence; Dickinson, Daniel S. -- 1800-1866 -- Correspondence; Douglas, Stephen A. -- 1813-1861 -- Correspondence; Doyle, Alexander, -- 1857-1922 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Ezekiel, Moses Jacob, -- 1844-1917 -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Gallaudet, Edward Miner, -- 1837-1917 -- Correspondence; Gardner, John Lane, -- 1793-1869 -- Correspondence; Gerolt, Friedrich Karl Joseph von, -- approximately 1798-1879 -- Correspondence; Gillet, Ransom H. -- 1800-1876 -- Correspondence; Harrison, Gabriel, -- 1818-1902 -- Correspondence; Henry, Joseph, -- 1797-1878 -- Correspondence; Humboldt, Alexander von, -- 1769-1859 -- Correspondence; Hunter, R. M. T. -- 1809-1887 -- Correspondence; Hyde, Anthony -- Correspondence; Johnson, Robert Ward, -- 1814-1879 -- Correspondence; Jones, George Wallace, -- 1804-1896 -- Correspondence; Jones, J. William -- 1836-1909 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; Lanman, Charles, -- 1819-1895 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Mason, J. M. -- 1798-1871 -- Correspondence; Morgan, Junius Spencer, -- 1813-1890 -- Correspondence; Peabody, George, -- 1795-1869 -- Correspondence; Renwick, James, -- 1818-1895 -- Correspondence; Riggs, Elisha, -- 1826-1881 -- Correspondence; Riggs, Lawrason, -- 1814-1884 -- Correspondence; Rorer, David, -- 1806-1884 -- Correspondence; Slaughter, Philip, -- 1808-1890 -- Correspondence; Story, William Wetmore, -- 1819-1895 -- Correspondence; Vail, Aaron, -- 1796-1878 -- Correspondence; Venable, Charles S. -- 1827-1900 -- Correspondence; Walker, Robert J. -- 1801-1869 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Wilson, James Grant, -- 1832-1914 -- Correspondence; Winthrop, Robert C. -- 1809-1894 -- Correspondence; Corcoran family; Corcoran family -- Correspondence; Baltimore and Ohio Railroad Company; Bank of America; Chesapeake and Ohio Canal Company; Corcoran & Riggs; Corcoran Gallery of Art; Little Miami Railroad Company; Philadelphia, Wilmington, and Baltimore Rail Road Company; Riggs and Co; Wilson, Colston & Co; Art museums -- Washington (D.C.)